2008
DOI: 10.1111/j.1365-2036.2008.03831.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of asymptomatic liver fibrosis in alcoholic patients using fibroscan: prospective comparison with seven non‐invasive laboratory tests

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(160 citation statements)
references
References 60 publications
9
150
0
1
Order By: Relevance
“…Castéra et al (9) and Colletta et al (10) have reported that detecting liver fibrosis by Fibroscan resulted in 84-95% of patients not requiring liver biopsy in 2005. Fibroscan has previously been used to evaluate the degree of liver fibrosis in patients with hepatitis B (11), hepatitis C (12,13) cirrhosis (14), alcoholic liver disease (15,16) and autoimmune liver diseases (17). It is also used in antiviral therapy efficacy evaluation (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Castéra et al (9) and Colletta et al (10) have reported that detecting liver fibrosis by Fibroscan resulted in 84-95% of patients not requiring liver biopsy in 2005. Fibroscan has previously been used to evaluate the degree of liver fibrosis in patients with hepatitis B (11), hepatitis C (12,13) cirrhosis (14), alcoholic liver disease (15,16) and autoimmune liver diseases (17). It is also used in antiviral therapy efficacy evaluation (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this discordance may come from the fact that the reviewed studies were conducted on a population with a heterogenous ethiology of cirrhosis. Pritchatt et al [22] demonstrated that in the HCV group (viral C cirrhosis) the number of false negative cases was significantly higher than in the non-HCV ethiology group (0.6% vs. 10.3%) while Nguyen-Khac et al [27] proved that the cut-off value is higher in alcoholic liver cirrhosis (19,5kPa) compared with the C viral cirrhosis (12,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)6kPa). …”
Section: Disscusionsmentioning
confidence: 99%
“…However, this point has been debated by some authors [15]. When there are no signs of severe acute alcoholic hepati-tis and if extensive fibrosis or cirrhosis is suspected, then the Fibrotest® [16]and FibroScan® [17] give satisfactory diagnostic performances.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%